(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2020)
The novel Coronavirus was recognised as causative pathogen of coronavirus outbreak in 2020. First case reported in Wuhan. Phylogenetic analysis suggests that an animal sold at seafood market is the host of new virus. Thousands of people already contracted with new coronavirus. The WHO declared the outbreak “public health emergency of international concern”. Coronavirus belongs to large family of virus which are zoonotic in nature. Signs of infection by this virus: respiratory diseases, fever, cough, dyspnoea, headache, hypoxemia, pneumonia, sore throat. Mode of transmission of SARS-CoV [2002] & MERS-CoV [2012] was by cat and dromedary camels. Coronavirus is causing severe acute respiratory syndrome indicated by elevated levels of aminotransferase and lymphopenia; alveolar damage can occur. Etiologic agents of respiratory diseases are human coronavirus: HKUI & HCOU-NL63 and for common cold, it is coronavirus OC43 & 229E. Murine coronavirus exhibit various levels of virulence and tropisms. Antibody & cell mediated responses needed for its prevention. Porcine coronavirus are cause of viral enteritis & foetal diarrhoea. The coronavirus spike protein- mediators cell-cell transmission. 1) Spike cleaves by proteases. 2) then enter cells by plasma membrane route. 3) finally replicate to particular cell based on ability to bind with receptors [2019 n-CoV – can bind to ACE-II receptors]. The demographic states: male: female sex ratio is 2.7-1 and age range 1-76 among the infected. Prevention include: regular hand washing, cover mouth while coughing, thoroughly cook meat and egg. The company Reckitt & Benckiser says that Dettol can kill some CoV strains.